Introduction to Facebook Marketing Campaigns - Carter, Brian (Que, 2011)
Want to get the most out of Facebook's powerful marketing features? This series reviews and guides you through the new Timeline profile, privacy concerns, places, check-in deals, pages, welcome tabs, fan gates, groups, advertising, credits and social plug-ins. Learn how to make your business look more appealing, get more fans, get more people to show up at your physical store, take advantage of affordable and powerful ways to reach new customers, stay on the cutting edge of social marketing, get more website visitors to fan your page, impress visitors with social proof of how customers love your brand, monitor what your competition is doing on Facebook, and how to stay ahead of them.